An evidence-based theory of change for reducing SARS-CoV-2 transmission in reopened schools. (July 2020) - Bonell, Chris; Melendez-Torres, G.J.; Viner, Russell M.; Rogers, M. Brooke; Whitworth, Michael; Rutter, Harry; Rubin, G. James; Patton, George
Abstract: Schools have closed worldwide as part of measures to prevent SARS-CoV-2 transmission but are beginning to reopen in some countries. Various measures are being pursued to minimise transmission but existing guidance has not developed a comprehensive framework or theory of change. We present a framework informed by the occupational health hierarchy of control and a theory of change informed by realist approaches. We present measures focused on elimination, substitution, engineering, administration, education and personal protective equipment. We theorise that such measures offer a means of disrupting SARS-CoV-2 transmission via routes involving fomites, faeco-oral routes, droplets and aerosols. Highlights: Schools have been closed worldwide to prevent SARS-CoV-2 transmission but are beginning to reopen in a number of countries. Existing guidance on measures to prevention transmission has not developed a comprehensive framework or theory of change. We present a framework for measures informed by the occupational health hierarchy of control and a theory of change. We theorise that, together, such measures offer a means of disrupting SARS-CoV-2 transmission.